Top priority characteristics of blue spaces design for stress reduction: a scoping review and Delphi technique among BlueHealth experts / Ammar Ayman Zaino, Jamalunlaili Abdullah and Aishath Rasiya - Zaino, Ammar Ayman; Abdullah, Jamalunlaili; Rasiya, Aishath (UiTM Press, 2025)
There is a growing need to identify blue space characteristics that optimize stress reduction. Few studies have directly linked specific variables of blue spaces to stress-reduction. To address this gap, this study aimed to develop a framework identifying priority blue space variables for stress reduction. A scoping review first compiled a comprehensive list of potentially influential factors. Using the Delphi technique, a qualitative study then evaluated the most significant of these variables through private interviews with eleven (11) BlueHealth experts. The experts, drawn from diverse disciplines, were asked to rate the importance of various blue space characteristics on a 6-point scale. The analysis revealed that factors such as size, colour/clarity, biodiversity, and time spent in the blue space may be the most critical for stress reduction. Experts highlighted the complex interrelationships between these variables, noting that the optimal design of blue spaces requires a delicate balance to maximize the stress-reducing potential. While further experimental validation is warranted, this expert-informed framework provides a solid foundation for designing blue spaces that support mental health and well-being. By prioritising the key variables and understanding their relative importance, architects, urban planners, and policymakers can make more informed decisions when creating or retrofitting blue spaces. The findings of this study come at a critical time, as the global mental health crisis continues to escalate, with depression and stress projected to be leading concerns by 2030. Integrating this evidence-based framework into the design of blue spaces holds the potential to mitigate the negative impacts of the built environment and contribute to the overall well-being of individuals and communities.